Orquestra Sinfônica da Paraíba: trajetória artística e dimensões socioculturais. - Nóbrega, Eduardo de Oliveira (2009)
This work presents the research results accomplished in the Symphonic Orchestra of Paraíba (OSPB) context. It has the objective to present the fundamental aspects that marked the OSPB Group trajectory, considering the social dimensions, politics and artistic that defined its characterization in the cultural scenery of João Pessoa City. The study was conceived starting from epistemic and methodological bases of the ethnomusicology area, and the collection of data was carry out starting from bibliographical researches, documental researches, web researches, questionnaires, interviews and observation of participants. The data analysis was consolidated in way to establish an accurate and systematic reading of the investigated reality. That research shows us, in an illuminated way, that the OSPB trajectory is marked by moments of stability and crises, and the political and social dimensions are definers of its artistic and cultural directions. In its current structure the Group demonstrates that, even due to difficult moments, it finds ways and subsidies for the accomplishment of its work. Finally, the research left evident that the Orchestra is recognized and valued by the João Pessoa society, but there are aspects in relation to the OSPB Group works that need more consistent politics for that in fact it can establish a true insert of its practice in the cultural city context.